Protein dynamics measurements by 3D HNCO based NMR experiments. Issue 1 (2002) - Xia Xia, Youlin Youlin; Sze Sze, Kong Hung Kong Hung; Li Li, Ning Ning; Shaw Shaw, Pang Chui Pang Chui; Zhu Zhu, Guang Guang
Abstract : Protein dynamics can be characterized by relaxation parameters obtained from traditional 2D HSQC based NMR experiments. This approach is hampered when applied to proteins with severe spectral overlap. In the present work, several novel 3D TROSY‒HNCO and 3D HSQC‒HNCO based NMR experiments were applied for measuring 15 N T 1, T 2 and 1 H‒ 15 N NOE with improved spectral dispersion by introducing a third 13 C dimension. The number of phase cycling steps in these 3D pulse sequences was restricted to two in order to minimize the time required to perform the dynamics measurements. For a uniformly 100% 15 N, 100% 13 C, and 70% 2 H‒labelled trichosanthin sample ( 27 kDa, 1.0 mM) at 30°C, the sensitivity of 3D TROSY‒HNCO based experiment was, on the average, enhanced by 72% compared to that of 3D HSQC‒HNCO based experiments. However, the 3D HSQC‒HNCO based experiments should be more effective for non‒deuterated proteins with smaller molecular weights and seriously overlapped 2D HSQC spectra. Results from the 3D TROSY‒HNCO and 3D HSQC‒HNCO based experiments were in good agreement with those obtained from traditional 2D HSQC based experiments.